Les particularités du rétinoblastome au Niger - Abba Kaka.H.Y; Sylla F; Ali M.H; Amza A (European Scientific Journal, ESJ, 2016)
Aims: To describe the clinical peculiarities of retinoblastoma and to outline the difficulties in their management in our context. Patients and Methods: We carried out a prospective study in all the cases of retinoblastoma from January 2014 to July 2015 in Niamey National Hospital. We studied: age, sex, first sign, age at first symptoms, time taken to seek medical help, anterior treatment , consanguinity, laterality, stage of tumor, extension of tumor, treatment done, survival rate. Results: The study was about 57 kids, among which 38 boys and 19 girls giving a sex ratio of 2.The mean age at diagnosis was 32 months with extremes of 7 months and 6 years. The range 2 to 3 years were most affected with 35 cases (61, 4%). Leucocorie was the onset symptom in 50 cases (87, 7%), strabismus in 7 cases (12, 3%). Traditional treatment was seen in 45 patients (79%). Consanguinity was found in 45 cases (79%), no family history of tumor was found in this study. In 38 cases (66, 66%) diagnosis was after one year of onset, the left eye was affected in 22 patients (38, 59%), the right eye in 21 patients (36, 84%) and it was bilateral in 14 cases (24, 56%). All our patients were at stage V of Reese classification, the tumor was extra-ocular in 54 patients (94, 6%) and intra-ocular in 5, 4% of cases. Enucleation was performed in 46 cases (80, 70%) and 56 patients (94, 73%) underwent chemotherapy cure. The survival rate after 18 months was of 15, 78%. Conclusion: Late presentation, diagnosis at an advance stage, and limited treatment options are the main factors responsible for the low rate of survival in this study.